Optimalisasi Pengelolaan M2 Homestay Melalui Pelatihan Excel dan Digitalisasi Laporan Usaha Penginapan - Sembiring, Nita; Ginting, Erwin; Sinaga, salsa; Sianturi, Charles; Fauzi, Muhammad; Yudi, Yudi (Publikasi Pengabdian Masyarakat, 2025)
The growth of the local tourism sector has encouraged the development of accommodation businesses such as homestays, including M2 Homestay, which is located in a strategic tourist area. However, the management of this homestay is still carried out conventionally, especially in terms of financial recording and business reporting, which are manually done and often inefficient. A lack of digital literacy is one of the main obstacles to implementing a technology-based management system. To address this issue, this community service program aimed to provide practical training in the use of Microsoft Excel and assist in the digitalization of business reports for the management of M2 Homestay. The implementation methods included direct training, the development of digital report templates, and hands-on assistance with the application of Excel-based recording systems. The results showed that the homestay manager gained basic skills in using Excel for business needs, including daily financial tracking, room occupancy records, and monthly reporting through visual graphs. The program had a noticeable impact, such as improved time efficiency in report preparation, greater accuracy in data recording, enhanced professionalism in business management, and increased awareness of the importance of digital tools in supporting business sustainability. This initiative demonstrates that simple technological interventions can significantly strengthen small tourism-based enterprises.